Quality of attractions and the satisfactions, benefits and behavioural intentions of visitors: verification of a model - Nowacki, Marek (Turyzm/Tourism, 2010)
The study is an attempt to verify a model of the relations between motivation, quality of attraction, benefits, satisfaction and the behavioural intentions of visitors to tourism attractions. The data for the analysis was collected from 582 visitors during the 10th Archaeological Festival at Biskupin. It was noted that the effect of the quality of the attraction on behavioural intentions leads to the benefits gained by the visitors. Benefits have a stronger total effect on behavioural intentions than visitor satisfaction.